1967
DOI: 10.1172/jci105596
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Glucose, Insulin, Inulin, and Evans Blue Protein into Thoracic Duct Lymph of Man*

Abstract: Summary. Immunoreactive insulin, like inulin, quickly equilibrates with interstitial fluid, as evidenced by recovery in thoracic duct lymph in man. Insulin-like activity not accounted for by immunoreactive insulin behaves as a large protein and is confined to the vascular compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 14 publications
5
38
0
Order By: Relevance
“…Drainage of the thoracic duct has previously been applied to reduce the number of circulating lymphocytes in order to induce systemic immunomodulation in autoimmune disorders and after organ transplantation; the amount of lymph collected per day was in the range of 1.5 to 2 L. When patients were examined after a meal or during a secretin test, the levels of the exocrine enzymes in the lymph rose prior to and to higher concentrations than those simultaneously measured in the blood, supporting the notion of a substantial direct delivery of these enzymes into the lymph capillaries adjacent to the acini (20,21). In line with the morphological observations reported here, corresponding measurements of insulin during an intravenous glucose tolerance test gave no support for a direct delivery of insulin into lymphatic capillaries (22).…”
Section: Discussionsupporting
confidence: 48%
“…Drainage of the thoracic duct has previously been applied to reduce the number of circulating lymphocytes in order to induce systemic immunomodulation in autoimmune disorders and after organ transplantation; the amount of lymph collected per day was in the range of 1.5 to 2 L. When patients were examined after a meal or during a secretin test, the levels of the exocrine enzymes in the lymph rose prior to and to higher concentrations than those simultaneously measured in the blood, supporting the notion of a substantial direct delivery of these enzymes into the lymph capillaries adjacent to the acini (20,21). In line with the morphological observations reported here, corresponding measurements of insulin during an intravenous glucose tolerance test gave no support for a direct delivery of insulin into lymphatic capillaries (22).…”
Section: Discussionsupporting
confidence: 48%
“…After three basal samples from Ϫ150 to Ϫ120 min, a continuous infusion of somatostatin (1.0 g ⅐ min Ϫ1 ⅐ kg Ϫ1 ; Bachem, Torrance, CA) was begun to suppress endogenous insulin secretion, and porcine insulin was infused into the femoral vein and maintained from Ϫ120 to 180 min for a total period of 5 h. During this insulin infusion, glucose was measured in 10-min intervals during the first 60 min and in 15-min intervals thereafter, and plasma glucose was clamped to basal levels by variable infusion of 50% glucose labeled with [3-3 H]-D-glucose (2.7 Ci/g glucose). Also, at 0 min, an intravenous bolus of [ 14 C]inulin (0.8 Ci/kg body wt) was given into a saphenous vein, and rapid samples for the measurement of the kinetic profile of [ 14 C]inulin were collected at 1, 2, 3, 4, 5,6,8,10,12,15,17,20,25,30,35,40,45,50, and 60 min and in 15-min intervals until the end of the experiment at 180 min. Protocol 2 (anesthetized study, sequential approach with interstitial fluid access).…”
Section: Methodsmentioning
confidence: 99%
“…The faster equilibrating compartment is assumed to be supplied by capillaries in the splanchnic bed that are porous and lack a continuous investment of the basement membrane, whereas skeletal muscle is assumed to account for a major component of the slowly equilibrating interstitial fluid compartment. Parameter k 01 represents the irreversible clearance of inulin from the plasma compartment by the kidney (18,20), and transport between plasma and slow (k 21 , k 12 ) and rapid (k 31 , k 13 ) equilibrating compartments was assumed to occur by passive diffusion (…”
Section: Pharmacokinetic Data Analysis: [mentioning
confidence: 99%
See 1 more Smart Citation
“…Lithell et al [32] also found increased insulin concentrations in the fasting state as well as at the end of an intravenous glucose tolerance test during b-blocking treatment, and the individual changes were inversely correlated with capillary density in skeletal muscle. The transendothelial insulin transport is an important regulator of the interstitial insulin concentration, which is normally lower than in plasma [33]. Changes in blood flow may thus affect the amount of insulin delivered to the interstitial fluid [34].…”
Section: Discussionmentioning
confidence: 99%